Evangelicalism, Sexual Morality, and Sexual Addiction: Opposing Views and Continued Conflicts - Edger, Kailla (Journal of religion and health, 2012)
While much of the Christian evangelical movement fosters judgmental attitudes surrounding sexuality, disapproving of other individuals who exhibit behaviors deemed morally reprehensible, other evangelical denominations embrace different viewpoints about human sexuality. In spite of the existence of ecumenical evangelical groups, the majority defines sexual morality through a narrow and prescriptive outlook and pathologizes certain sexual behaviors. Solutions to identified sexual problems are often provided through restrictive viewpoints despite the existence of largely opposing positions within this movement. Reaction formation and authoritarian personality theory are theorized as the primary explanations for individuals failing to conform to stringent religious sexual expectations.